Hybrid planning of distributed generation and distribution automation to improve reliability and operation indices - Pirouzi, Sasan; Zaghian, Masoud; Aghaei, Jamshid; Chabok, Hossein; Abbasi, Mohsen; Norouzi, Mohammadali; Shafie-khah, Miadreza; Catalao, Joao P.S. (Elsevier, 2022)
This paper intends to give an effective hybrid planning of distributed generation and distribution automation in distribution networks aiming to improve the reliability and operation indices. The distribution automation platform consists of automatic voltage and VAR control and automatic fault management systems. The objective function minimizes the sum of the expected daily investment, operation, energy loss and reliability costs. The scheme is constrained by linearized AC optimal power flow equations and planning model of sources and distribution automation. A stochastic programming approach is also implemented in this paper based on a hybrid method of Monte Carlo simulation and simultaneous backward method to model uncertainty parameters of the understudy model including load, energy price and availability of network equipment. Finally, the proposed strategy is implemented on an IEEE 69-bus radial distribution network and different case studies are presented to demonstrate the economic and technical benefits of the investigated model. By allocating the optimal places for sources and distribution automation across the distribution network and extracting the optimal performance, the proposed scheme can simultaneously enhance economic, operation, and reliability indices in the distribution system compared to power flow studies.
Keywords: Distribution automation; Mixed integer linear programming; Operation indices; Reliable planning; distributed generation; fi=Sähkötekniikka|en=Electrical Engineering|